Overview of Thirst Level in Pre-Operative Patients - Muhammad Pandu Wira Sena Isnantopo, Noor; Sukmaningtyas, Wilis; Triyudono, Danang (Java Nursing Journal, 2024)
Background: Fasting before surgery has the effect of reducing the acidity and volume of the stomach which affects the risk of nausea and vomiting leading to aspiration pnomonia and gastric regurgitation that may occur during anesthesia. Purpose: The study aims to determine the description of the level of thirst in preoperative patients at the Central Surgical Installation (IBS) of Dr. H. Moch. Ansari Saleh Banjarmasin Hospital. Methods: This study used descriptive method with cross sectional design. The sampling technique with total sampling obtained 35 respondents. Data analysis using descriptive analysis. Findings: The study showed 18 respondents (51.4%) had fasted for 5-8 hours before surgery, 13 respondents (37.1%) had a habit of drinking more than 2000 ml of water per day, this study showed that the level of thirst of respondents in the mild category was 31.4%, the level of moderate thirst was 42.9% and the level of severe thirst was 25.7%. Conclusion: That more respondents experienced moderate thirst.